Effects of Plant-Derived Glycerol Monolaurate (GML) Additive on the Antioxidant Capacity, Anti-Inflammatory Ability, Muscle Nutritional Value, and Intestinal Flora of Hybrid Grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂) - Li, Xuehe; Yi, Yuanming; Wu, Jiahua; Yang, Qihui; Tan, Beiping; Chi, Shuyan (Metabolites, 2022)
In a context where the search for plant-derived additives is a hot topic, glycerol monolaurate (GML) was chosen as our subject to study its effect on grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂). Seven gradient levels of GML (0, 600, 1200, 1800, 2400, 3000, and 3600 mg/kg) were used for the experiment. Based on our experiments, 1800 mg/kg GML significantly increased the final body weight (FBW) and weight gain rate (WGR). GML increased the activity of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and decreased malondialdehyde (MDA). Adding 1800 mg/kg GML also significantly increased the levels of lauric acid (C12:0) (LA), n-3 polyunsaturated fatty acids (PFA), and the n-6 PFA-to-n-3/n-6 ratio, while significantly decreasing the levels of saturated fatty acids (SFA). Dietary supplementation with GML significantly inhibited the expression of pro-inflammatory factors and reduced the occurrence of inflammation. GML improved intestinal flora and the abundance of beneficial bacteria (Bacillus, Psychrobacter, Acinetobacter, Acinetobacter, Stenotrophomonas, and Glutamicibacter). It provides a theoretical basis for the application of GML in aquafeed and greatly enhances the possibility of using GML in aquafeed. Based on the above experimental results, the optimum level of GML in grouper feed is 1800 mg/kg.